Google Trends Analysis on Investor Sentiment on Stock Return Jakarta Islamic Index - Meylianingrum, Kurniawati; Kholilah, Kholilah; Jaya, Tiara Juliana (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2023)
Investor sentiment arises when there is an event or event that affects people's lives such as pandemics, terrorism, wars, and economic conditions. The Covid 19 pandemic is an outbreak that has emerged and its spread is very fast around the world, so it requires people to stay at home to reduce the rate of transmission. This research was conducted to find out the positive and negative sentiment of investors towards the return of Jakarta Islamic Index shares. Positive and negative sentiment is induced from medical terms that appear on the google trends page. The method carried out is to use quantitative with a descriptive approach. The results obtained in this study are that investor sentiment, both positive and negative, partially and simultaneously has a significant positive effect on stock returns on the Jakarta Islamic Index. This shows that if there is a trust issue that is happening such as covid-19, war, data breaches, it can make investor sentiment change in choosing companies that issue stocks with data evidence taken from Google Trends to analyze the popularity of queries with keywords entered into search engines.